The near wake of a model horizontal-axis wind turbine at runaway - Ebert, P.R.; Wood, D.H. (Renewable energy, 2002)
This paper completes a series which describes measurements within two chord lengths of the blades of a small horizontal-axis wind turbine over a wide range of operating conditions. Prior to the present experiment, the turbine was rebuilt to allow operation at its runaway point, where no power is produced. Runaway can be viewed as the upper limit on wind turbine performance at which thrust and wake expansion are maximised. The measurements, which approximate the mean and fluctuating velocity fields seen by an observer rotating with the blades, were obtained from a stationary X-probe hot-wire anemometer by the technique of phase-locked averaging. It is shown conclusively that there is negative (power-producing) angular momentum extracted from the wake, but a balancing positive angular momentum resides in the tip vortices. The mean velocity through the blades increases significantly with radius, in contrast to the near-constant velocity when the turbine is producing its maximum power. Comparisons with conventional blade calculations suggest that the circulation in the wake is related to the difference between the circumferential components of the lift and drag, rather than the magnitude of the lift as is often assumed. Within the range and accuracy of measurement, the pitch of the tip vortices is constant and proportional to the inverse of the tip speed ratio.